Code-switching of Chinese students at the tertiary level in conversations: concerning English - Al-Nahdi, Yousef Ali Ahmed Saleh; Shuo, Zhao; Firdous, Tehmina (Technium Social Sciences Journal, 2022)
We examined Chinese university students' daily-life casual attitudes regarding code-switching of English. It challenges students' everyday and simple conversations. Code-switching is "the use of two or more languages within the same conversation, usually within the same conversational turn, or even within the same sentence. According to the study, code-switching is a combination of two languages used during the same auditory communication or conversation between Chinese University students. An interview sample of students represents one of the public universities in Beijing. Participants included 42 Chinese students from various majors, including journalism, media, communication, drama, and languages. This study involved a questionnaire containing 21 questions. According to the study, there was an evident shortage of English code-switching features among this population. To say it differently, they rarely use code-switching, as they are afraid of conveying a wrong meaning, and using Chinese is easier and more convenient.